BLACK WOMEN: DECOLONIZING NARRATIVES (PRÁXIS EM SAÚDE, 2025)
This qualitative study, grounded in the Free Association Narrative Interview and psychoanalysis, aims to testify how structural racism shapes the trajectory of Black women working as domestic workers and nannies for white families. The results, based on the life story of the interviewee, identified two thematic categories of analysis that revealed transgenerational psychoanalytic patterns: Expressions of Colonial Superiority, which articulates Fanonian dehumanization and Ferencz’s communicational shock of “language confusion”; and Oscillation of the Black Mother, which exposes the festive–subservient ambivalence described by Lélia Gonzalez. It is argued that giving voice to memories and re-signifying colonial narratives promotes subjective decolonization, opening pathways for therapeutic practices that restore care, autonomy, and recognition to Black women.
Keywords: Black Women; Racism; Colonial Trauma